Regularities of calcium dialuminate synthesis in the process of solid-phase synthesis from aluminum micro- and nanopowders; Ceramics International; Vol. 51, iss. 25, pt. A - Tokarev D. S. Denis Sergeevich; Mostovshchikov A. V. Andrey Vladimirovich; Nikolaeva A. N. Anastasiya Nikolaevna; Nazarenko O. B. Olga Bronislavovna (2025, 2025)
Title screen